Root exposure to apple replant disease soil triggers local defense response and rhizoplane microbiome dysbiosis. Issue 4 (15th February 2021) - Balbín-Suárez, Alicia; Jacquiod, Samuel; Rohr, Annmarie-Deetja; Liu, Benye; Flachowsky, Henryk; Winkelmann, Traud; Beerhues, Ludger; Nesme, Joseph; J. Sørensen, Søren; Vetterlein, Doris; Smalla, Kornelia
ABSTRACT: A soil column split-root experiment was designed to investigate the ability of apple replant disease (ARD)-causing agents to spread in soil. 'M26' apple rootstocks grew into a top layer of Control soil, followed by a barrier-free split-soil layer (Control soil/ARD soil). We observed a severely reduced root growth, concomitant with enhanced gene expression of phytoalexin biosynthetic genes and phytoalexin content in roots from ARD soil, indicating a pronounced local plant defense response. Amplicon sequencing (bacteria, archaea, fungi) revealed local shifts in diversity and composition of microorganisms in the rhizoplane of roots from ARD soil. An enrichment of operational taxonomic units affiliated to potential ARD fungal pathogens ( Ilyonectria and Nectria sp.) and bacteria frequently associated with ARD ( Streptomyces, Variovorax ) was noted. In conclusion, our integrated study supports the idea of ARD being local and not spreading into surrounding soil, as only the roots in ARD soil were affected in terms of growth, phytoalexin biosynthetic gene expression, phytoalexin production and altered microbiome structure. This study further reinforces the microbiological nature of ARD, being likely triggered by a disturbed soil microbiome enriched with low mobility of the ARD-causing agents that induce a strong plant defense and rhizoplane microbiome dysbiosis, concurring with root damage. Abstract : Soil–plant feedback loop: local rhizoplane microbiome–phytoalexin interaction.